Outcome of synthetic adrenocorticotropin hormone treatment in children with infantile spasm - I Gusti Ngurah Made Suwarba (Paediatrica Indonesiana, 2011)
Background Infantile spasms (IS) is an age-spedfic epilepsy syndrome characterized by flexor, extensor, and mixed flexor-extensor spasms which often occur in clusters during the first 2 years of life. IS is often difficult to manage 'With the usual anti-epilepsy drugs (AEDs). Therapy with adrenocorticotropin honnone (ACTH) has been used since 1958. In Indonesia, ACTH usage is still rare.Objective This study aims to examine the effectiveness of ACTH as an anti-epileptic drug in managing IS.Methods This was descriptive retrospective cohort study. Subjects were IS patients who visited the neurology outpatient clinic in Sanglah Hospital, Bali, from January 2007 until June 2010. Each subject received AED(s) plus either ACTH or methylprednisolone for 4ô€†6 weeks.Results There were 19 IS patients over the four year duration of this study. They were mostly boys (11), aged 2 weeks to 17 months, with a mean age at treatment of 9 months. Eighteen patients received poly therapy, while one patient received only phenobarbital as monotherapy. Most patients who received ACTH (13/16) had a seizure-free period, while the 3 that did not receive ACTH continued having seizures. Patients who received ACTHshowed a good response (seizure-free) after 5-13 days therapy and their EEG pattern showed disappearance of burst suppression Mthin 1-2 weeks. ACTH side effects included weight gain and cushingoid appearance. One patient died from pneumonia.Conclusions Diagnosis of IS should be considered in patients pre-senting Mth spasms at less than 6 months old. IS treatment should begin as soon as possible. IS patients responded well to a short course of ACTH therapy.Â